ANALISIS NILAI KARAKTER LAGU ANAK KARYA ABDULLAH TOTONG MAHMUD PADA BUKU SISWA KELAS II SD/MI KURIKULUM 2013 - Badi’atul Azizah; Fillia Prima Artharina; Sukamto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Anarchist behavior, strife and brawls, vigilantism, an increasingly free transformation of global ethics, drug abuse if examined carefully, all begin ina crisis of morality. This is a problem in the life of society, nation, and state so that through character education programs applied in the scope of education can be a solution or solution. One of the efforts to instill character values in elementary school children can be done through children's songs. This study aims to determine and analyze the character values contained in the lyrics of children's songs by Abdulloh Totong Mahmud in the book of grade II elementary / mi students curriculum 2013. This research method uses a qualitative descriptive approach with literature research methods. The research subjects studied were thirteen children's songs by A.T Mahmud in the 2013 Curriculum Grade II student book. Based on the results of this study (1) religious values are found in happy songs of gathering, throwing garbage, rainbows, fireflies, cypresses, uncle come, scenery, thank God and the moon (2) nationalist values are found in father's bell songs (3) independent values are found in happy songs of gathering, rowing, my chicken, lizards (4) mutual aid values are contained in happy songs gathering (5) The value of integrity is contained in the song of throwing garbage.